2020
DOI: 10.1044/2020_jslhr-20-00013
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors of Levator Veli Palatini Muscle Contraction During Speech Using Dynamic Magnetic Resonance Imaging

Abstract: Purpose The purpose of this study was to identify predictors of levator veli palatini (LVP) muscle shortening and maximum contraction velocity in adults with normal anatomy. Method Twenty-two Caucasian English-speaking adults with normal speech and resonance were recruited. Participants included 11 men and 11 women ( M = 22.8 years, SD = 4.1) with normal anatomy. Static magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Targeted recruitment in select CSD studies (e.g., Cycyk & Huerta, 2020;Jasso et al, 2020;Orizaba et al, 2020) appears to have successfully contributed to expanded representation for Hispanic or Latino(a)(x) participants, at least for specific research questions regarding Latino(a)(x) culture and Spanish-English multilingual issues. In contrast, we found just three studies (Caesar & Kerins, 2020;Girolamo et al, 2020;Pua et al, 2020) to recruit according to participant race. Therefore, it seems as though there may be missed opportunities, worth exploring in future studies, for research in CSD to conduct investigations within racial groups for a deeper and more nuanced understanding of characteristics and best practices within various populations.…”
Section: Recruiting For Proportional Versus Targeted Representationmentioning
confidence: 86%
“…Targeted recruitment in select CSD studies (e.g., Cycyk & Huerta, 2020;Jasso et al, 2020;Orizaba et al, 2020) appears to have successfully contributed to expanded representation for Hispanic or Latino(a)(x) participants, at least for specific research questions regarding Latino(a)(x) culture and Spanish-English multilingual issues. In contrast, we found just three studies (Caesar & Kerins, 2020;Girolamo et al, 2020;Pua et al, 2020) to recruit according to participant race. Therefore, it seems as though there may be missed opportunities, worth exploring in future studies, for research in CSD to conduct investigations within racial groups for a deeper and more nuanced understanding of characteristics and best practices within various populations.…”
Section: Recruiting For Proportional Versus Targeted Representationmentioning
confidence: 86%
“…Results from the present study indicate that pharyngeal depth may serve as a strong clinical determinant of VPD in children with 22q11.2DS. Dynamic MRI studies in individuals with normal velopharyngeal anatomy indicated that increased velar thickness resulted in decreased levator muscle shortening and contraction velocity 29 and that a larger velopharyngeal opening required increased levator activation and closure force to achieve velopharyngeal closure. 30 Findings from the present study indicate that in children with 22q11.2DS, a deep pharynx is correlated with greater levator muscle shortening and increased effective velar stretch.…”
Section: Differences Across Conditionsmentioning
confidence: 99%
“…Subsequent studies, often using MRI, frequently report measures of curvilinear velar length. 1–3,15,17–19,21,42–47 Nasal surface measures of velar length during phonation have also been reported. 36,48,49 However, variability, both in the definitions provided and measurement technique applied for velar length, is consistently observed across the literature.…”
Section: Introductionmentioning
confidence: 97%